Antibacterial effects of human mesenchymal stem cells and their derivatives: a systematic review - Castro Ramos, Adeline; Widjaja Lomanto, Markus Yovian; Vuong, Cat-Khanh; Ohneda, Osamu; Fukushige, Mizuho (Frontiers in Microbiology, 2024)
Introduction: The growing problem of antimicrobial resistance (AMR) poses a significant challenge to public health; This is partly due to the lack of advancements in the development of novel antibiotics and the pressing need for alternative treatment options. Mesenchymal stem cells (MSC) possess secretory components that enhance the immune response and peptides that disrupt the bacteria constitution. The isolation of various human tissues has facilitated the investigation of the diverse potentials of MSC and their components. Further research is needed to fully understand the spectrum and efficacy of these elements and their differences. The primary aim of this study was to perform a thorough review of the current literature related to the antimicrobial properties of MSC and their associated components. The objective was to establish an insight into the results and effects of utilizing MSC in relation to bacterial colonization, and to present an overview of previously documented findings. Methods: This systematic literature review was conducted using the PubMed, Embase, and Web of Science databases. Data on the effect of MSC or their derivatives were measured by calculating the percentage of bacterial counts reduction after treatment with MSC in comparison to the control. Results: A total of 3,911 articles were screened, and 31 eligible publications were selected for inclusion in the analysis. In the current systematic review, the majority of the experimental designs showed positive outcomes in terms of bacterial load reduction when MSC or their derivatives were used, with bone marrow being the most effective tissue. The rest of the findings exhibited heterogeneity in the spectrum of outcomes that could be attributed to the effects of using various tissues derived MSC in both in vivo and in vitro studies. Conclusion: The findings of our study indicate the potential antibacterial characteristics of MSC. The direct antimicrobial activity of these cells was demonstrated by our results, which quantitatively showed a decrease in bacterial growth after treatment with MSC. However, additional research is required to clarify the factors that determine the efficacy of their antimicrobial activity and their various components.